2023
DOI: 10.1007/s00239-023-10094-4
|View full text |Cite
|
Sign up to set email alerts
|

Embracing Complexity: Yeast Evolution Experiments Featuring Standing Genetic Variation

Abstract: The yeast Saccharomyces cerevisiae has a long and esteemed history as a model system for laboratory selection experiments. The majority of yeast evolution experiments begin with an isogenic ancestor, impose selection as cells divide asexually, and track mutations that arise and accumulate over time. Within the last decade, the popularity of S. cerevisiae as a model system for exploring the evolution of standing genetic variation has grown considerably. As a facultatively sexual microbe, it is possible to initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…We therefore turned to experimental evolution as an alternative approach to improve the hybrids’ fermentative profiles. Experimental evolution across multiple generations, paired with time-series whole genome sequencing, is a powerful tool for studying microbial responses to a selective environment and to understand the fitness effects of de novo mutations (Barrick & Lenski, 2013; Burke, 2023; Cooper, 2018; Maddamsetti et al, 2015). We found that, after 250 generations in a high sugar and ethanol environment, hybrids evolved faster fermentation performance and higher ethanol production compared to both parents and ancestral unevolved hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore turned to experimental evolution as an alternative approach to improve the hybrids’ fermentative profiles. Experimental evolution across multiple generations, paired with time-series whole genome sequencing, is a powerful tool for studying microbial responses to a selective environment and to understand the fitness effects of de novo mutations (Barrick & Lenski, 2013; Burke, 2023; Cooper, 2018; Maddamsetti et al, 2015). We found that, after 250 generations in a high sugar and ethanol environment, hybrids evolved faster fermentation performance and higher ethanol production compared to both parents and ancestral unevolved hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore turned to experimental evolution as an alternative approach to improve the hybrids’ fermentative profiles. Experimental evolution across multiple generations, paired with time-series whole genome sequencing, is a powerful tool for studying microbial responses to a selective environment and understanding the fitness effects of de novo mutations [ 24 26 , 77 ]. We found that, after 250 generations in a high sugar and ethanol environment, hybrids evolved faster fermentation performance and higher ethanol production compared to both parents and ancestral unevolved hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the already high species-specific recombination rates (Liu et al 2019), as well as this extra selection for high rates of outcrossing, regions of linked alleles that may potentially respond to experimental evolution are expected to be relatively small in the population (as small as 5-10KB; cf. Burke 2023). The experimental populations featured in this study were then derived from samples of this base population: 20 control replicates (C 1-20 ), 20 moderate ethanol stress replicates (M 1-20 ), and 20 high ethanol stress replicates (H 1-20 ).…”
Section: Methodsmentioning
confidence: 99%